Perbandingan Kesejahteraan Antara Pengusaha dan Pegawai Perspektif Maqashid Syariah di Kelurahan Kejawan Putih Tambak Surabaya - Khea Miyagi; Muhammad Nafik HR (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to identify and analyze Comparison Between Employers and Employees Welfare maqashid Shariah Perspective in the Village Kejawan Putih Tambak Surabaya. That is the basis of interview questions to determine the welfare comparison between employers and employees in terms of five aspects, namely, religion, life, intellect, lineage and property.This study used a qualitative approach with ethnographic strategy. Data was collected through interviews and direct observation to study the object. The analysis technique used is descriptive qualitative analysis narrate the results of interviews and direct observation.The results of this study is that there is little difference between employers and employee welfare. The welfare of employers better meet the criteria Maqashid Shariah Perspective. The employers have more time to gather with family, having time to pray in the mosque, pay more attention to their health and have more social activities than employees. While employees have limited time togather with family, can not pray in a timely manner, rarely have time to socialize and do not have time for a workout. Therefore employers mental welfare is better than employees. REFERENCESAbdul, Hakim. 2013. Pengaruh Dana Bantuan Langsung Masyarakat Terhadap Penyerapan Tenaga Kerja dan Perkembangan Usaha Tani Padi Serta Kesejahteraan Keluarga Petani Kabupaten Kota di Provinsi Nusa Tenggara Barat Dalam Perspektif Islam. Disertasi tidak diterbitkan. Pascasarjana Universitas Airlangga.Abraham H. Maslow. 1994. Motivasi dan Kepribadian 1. (Teori Motivasi dengan Pendekatan Kebutuhan Manusia). Jakarta. PT. PBPAl-Qur’an Tafsir dan Terjemahannya. 1978. Bandung: Firma Sumatra Bandung Lembaga Penterjemah dan Tafsir Al-Qur’an.Badewi, Zaki Ahmad. 1982. Mu’jam Mushthalahâtu al-‘Ulûm alIjtimâ’iyyah, (Beirut, Maktabah Lubnan : New Impression)Bakri, Jaya Asyafri. 1996. Konsep Maqashid Syari’ah menurut Syaitibi, Jakarta: Raja Grafindo Persada.Basrowi. 2011. Kewirausahaan untuk Perguruan Tinggi. Bogor. Ghalia IndonesiaBoediono. 2002. Ekonomi Mikro. BPFE. YogyakartaDepdiknas.2008. Kamus Bahasa Indonesia, Jakarta : Pusat BahasaDiola, Alfa. 2011. “Peran Baitul Maal Wat Tamwil Dalam Meningkatkan Kesejahteraan Anggota Pada BMT –UGT SIDOGIRI di Kota Surabaya”. Skripsi tidak diterbitkan. FakultasEkonomi dan Bisnis, Universitas Airlangga.Djamil, Fathurrahman. 1995. Metode Ijtihad Majlis Tarjih Muhammadiyah.Jakarta: Logos Publishing House.Heryawan, Ahmad. 2009. “Kesejahteraan dan Ukurannya”, (Online), (http://ahmadheryawan.blogspot. co.id/kesejahteraan-dan-ukuran, Diakses pada 1 april 2012)Karim, Adiwarman. 2007. “Ekonomi Mikro Islami". EdisiKetiga. Jakarta: PT Raja Grafindo Persada.Michael P. Todoro. 2000. Ekonomi untuk Negara Berkembang. Jakarta. Bumi AksaraMidgley, James, Martin B. Tracydan Michelle Livermore (ed). The Hanbook of Social Policy. London : Page, halaman xiMoleong, Lexy J.1988. Metodologi penelitian kualitatif. Edisi Revisi. Bandung : Remaja RosdakaryaMuhammad Quraish Syihab. Wawasan AlQur’an. Bandung : Mizan, 1996Nazir, Mohammad. 2003. Metode Penelitian. Jakarta: Ghalia Indonesia.Undang-Undang Republik Indonesia No. 11 Tahun 2011 Tentang Kesejahteraan SosialRiyandno, Muhammad Nafik H. 2010. Rasionalitas Konsumsi Muslim. Program Studi Ekonomi Islam, Fakultas Ekonomi Universitas Airlangga, disampaikan pada kuliah Seminar Ekonomi Islam.Spradley, James P. 1997. Metode Etnografi. Terjemahan oleh Misbah ZulfaTasmara, Toto. 2002. Membudayakan Etos Kerja Islami. Jakarta. Gema Insani.Widiastuti, Tika. 2008, “Dampak korupsi terhadap tingkat kesejahteraan masyarakat di beberapa negara muslim”. Tesis tidak diterbitkan. Program Pasca Sarjana Universitas Indonesia.Widjaja, A.W. 2006. Administrasi Kepegawaian. Jakarta. RajawaliZadjuli, Suroso Imam. 2008. Prinsip-prinsip Ekonomi Islam. Surabaya: FE Unair